2021
DOI: 10.1513/annalsats.202007-886oc
|View full text |Cite
|
Sign up to set email alerts
|

Association between Tunneled Pleural Catheter Use and Infection in Patients Immunosuppressed from Antineoplastic Therapy. A Multicenter Study

Abstract: word count: 281/350 Tables and figures: 5 (2 supplementary tables) Title: Association between tunneled pleural catheter use and infection in patients immunosuppressed from antineoplastic therapy: a multicenter study (128/130 characters with spaces) Short title: Tunneled pleural catheter use in immunosuppression (50/50 characters with spaces)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
(69 reference statements)
2
8
0
1
Order By: Relevance
“…In addition, the reported median time was 41 (interquartile range 19–87) days, and neither antineoplastic therapy nor immunocompromised state increased the risk of IPC‐related infection according to a multicenter study of 1408 IPCs among 1318 patients with MPE. 59 These investigators’ conclusions were consistent with those of Mekhaiel et al 60 …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, the reported median time was 41 (interquartile range 19–87) days, and neither antineoplastic therapy nor immunocompromised state increased the risk of IPC‐related infection according to a multicenter study of 1408 IPCs among 1318 patients with MPE. 59 These investigators’ conclusions were consistent with those of Mekhaiel et al 60 …”
Section: Discussionsupporting
confidence: 81%
“…In addition, the reported median time was 41 (interquartile range 19-87) days, and neither antineoplastic therapy nor immunocompromised state increased the risk of IPC-related infection according to a multicenter study of 1408 IPCs among 1318 patients with MPE. 59 These investigators' conclusions were consistent with those of Mekhaiel et al 60 Methods to prevent and effectively treat postoperative infection, in addition to primary disease management, are high priorities. Zhao et al studied 128 patients with MPE under focused preventive interventions, including maintaining an aseptic field throughout the surgical process, educating patients about normative IPC use, monitoring wound conditions, and regularly changing wound dressing and drainage bags; these significantly reduced IPC-related infection incidence from 13% to 5%.…”
Section: F I G U R Esupporting
confidence: 64%
“…In a large multicentre retrospective review of 1021 patients treated with IPC, pleural space infections specifically developed in 50 (4.9%) patients with an overall mortality risk of 0.3% [109], significantly lower than standard pleural infection. In another large multicentre series (n=1318), WILSHIRE et al [110] recently found a similar infection rate (6-7%) but importantly also showed that the risk of IPC-related infection did not appear to be increased by antineoplastic therapy use or an immunocompromised state. In multivariable competing risk analyses they found longer IPC in situ duration to be associated with a higher risk of infection [110].…”
Section: Indwelling Pleural Catheters and Pleural Infectionmentioning
confidence: 75%
“…In another large multicentre series (n=1318), WILSHIRE et al [110] recently found a similar infection rate (6-7%) but importantly also showed that the risk of IPC-related infection did not appear to be increased by antineoplastic therapy use or an immunocompromised state. In multivariable competing risk analyses they found longer IPC in situ duration to be associated with a higher risk of infection [110].…”
Section: Indwelling Pleural Catheters and Pleural Infectionmentioning
confidence: 75%
See 1 more Smart Citation